Effects of dry period length on milk production and energy balance in two cow breeds. (10th August 2017) - Andrée O'Hara, E.; Omazic, A.; Olsson, I.; Båge, R.; Emanuelson, U.; Holtenius, K.
Abstract : Shortening the dry period (DP) has been proposed as a strategy to improve energy balance (EB) in cows in early lactation. This study evaluated the effects of shortening the DP on milk yield (MY), EB and residual feed intake (RFI) in two breeds; Swedish Red (SR) and Swedish Holstein (SH). Cows were blocked by breed and parity and then randomly assigned to one of two treatments; short DP of 4 weeks (4W, n =43) or conventional DP of 8 weeks (8W, n =34). Cows were kept and fed under the same conditions, except for the 4 weeks when the 4W group were still lactating prepartum and thus kept with the lactating cows. Milk yield and BW were recorded and body condition score (BCS) was rated from 10 weeks prepartum to 12 weeks postpartum . Dry matter intake (DMI) was recorded for lactating cows postpartum . Milk yield was reduced by 6.75 kg/day during the first 12 weeks postpartum ( P <0.001) for the 4W cows compared with 8W cows, but there was no significant difference in total MY (3724 kg compared with 3684 kg, P =0.7) when the milk produced prepartum was included. Protein content was higher in 4W cows (3.42%) than in 8W cows (3.27%) ( P <0.001) postpartum . In the 8W group, cows lost more BCS after calving ( P <0.05). Cows of SR breed had higher BCS than cows of SH breed (SR=3.7, SH=3.2, P <0.001), but no differences in BW were found between breed and treatment. Energy balance was improved for cows in the 4W group ( P <0.001), while feed efficiency, expressed as RFI, was reduced for 4W cows than for 8W cows (5.91 compared with −5.39, P <0.01). Shortening the DP resulted in improved EB postpartum with no difference between the breeds and no milk losses when including the milk produced prepartum .